2020
DOI: 10.1126/sciadv.aba8940
|View full text |Cite
|
Sign up to set email alerts
|

Human footprints provide snapshot of last interglacial ecology in the Arabian interior

Abstract: The nature of human dispersals out of Africa has remained elusive because of the poor resolution of paleoecological data in direct association with remains of the earliest non-African people. Here, we report hominin and non-hominin mammalian tracks from an ancient lake deposit in the Arabian Peninsula, dated within the last interglacial. The findings, it is argued, likely represent the oldest securely dated evidence for Homo sapiens in Arabia. The paleoecological evidence indicates a well-watered semi-arid gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 144 publications
0
45
0
Order By: Relevance
“…Modern human fossils have been recovered in northeastern Africa and the Levant that date back to these times 4,5 . Moreover, human occupation layers in the Sodmein cave in the Eastern Egypt desert 53 and artefacts and human fossils from Al Wusta in Saudi Arabia 54 , Skhul and Quafzeh 55 as well as human footprints in ancient lake sediments 56 also fall into MIS 5. These time windows have also been proposed by population modelers as possible episodes for early modern human expansion 57 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Modern human fossils have been recovered in northeastern Africa and the Levant that date back to these times 4,5 . Moreover, human occupation layers in the Sodmein cave in the Eastern Egypt desert 53 and artefacts and human fossils from Al Wusta in Saudi Arabia 54 , Skhul and Quafzeh 55 as well as human footprints in ancient lake sediments 56 also fall into MIS 5. These time windows have also been proposed by population modelers as possible episodes for early modern human expansion 57 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we conduct a detailed taphonomic analysis of a large wild carnivore-accumulated bone assemblage from the Umm Jirsan lava tube located in the Harrat Khaybar lava field, northern Saudi Arabia. Despite growing evidence for the importance of the Arabian Peninsula in human (and hominin) history and prehistory (e.g., Delagnes et al 2012;Groucutt and Petraglia 2012;Groucutt et al 2018;Stewart et al 2020;Petraglia et al 2015), only a single carnivore neo-taphonomic study has been conducted for the entire peninsula: a study of a small possible striped hyena accumulation from the coast of Qatar (Andrews 2008). Exploratory work has shown that bones in the Umm Jirsan lava tube system date from at least ~ 4.5 ka to recent times (Pint 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Footprints provide invaluable data on the number individuals who made them and on their biological (stature, age, body mass) and biomechanical (posture, gait, speed) characteristics 2 5 . However, and despite important recent discoveries 5 9 , the number of sites with such footprints remains relatively uncommon compared to archaeological or palaeoanthropological sites, especially for those occupied by Neandertals 5 . This is the case of the Iberian Peninsula, where there are several localities with osteological and technological remains of Neandertals 10 12 , but only one potential poorly preserved footprint in the dune complex from Catalán Bay (28,000 years) at Gibraltar 13 .…”
Section: Introductionmentioning
confidence: 99%